2009
DOI: 10.1016/j.sbi.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry in the analysis of N-linked and O-linked glycans

Abstract: Mass spectrometry continues to play a vital role in defining the structures of N-and O-glycans in glycoproteins via glycomic and glycoproteomic methodologies. The former seeks to define the total N-and/or O-glycan repertoire in a biological sample whilst the latter is concerned with the analysis of glycopeptides. Recent technical developments have included improvements in tandem mass spectrometry (MS/MS and MS n ) sequencing methodologies, more sensitive methods for analysing sulfated and polysialylated glycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
166
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(167 citation statements)
references
References 49 publications
0
166
0
1
Order By: Relevance
“…Glycosylation is one of the most common and important post-translational modifications of proteins, yet it is also one of the most difficult to study because of its great complexity. Much of what we know about glycosylation, especially tissueand organism-specific variation, has been gathered via mass spectrometric profiling of detached glycans (1)(2)(3)(4). International, multi-laboratory comparisons of MS 1 and chromatographic glycomic data derived from standardized glycoproteins have concluded that the MS analysis of permethylated derivatives of released N-and O-linked glycans is the most robust glycomics strategy with respect to both sensitivity and quantitative reliability (5,6).…”
mentioning
confidence: 99%
“…Glycosylation is one of the most common and important post-translational modifications of proteins, yet it is also one of the most difficult to study because of its great complexity. Much of what we know about glycosylation, especially tissueand organism-specific variation, has been gathered via mass spectrometric profiling of detached glycans (1)(2)(3)(4). International, multi-laboratory comparisons of MS 1 and chromatographic glycomic data derived from standardized glycoproteins have concluded that the MS analysis of permethylated derivatives of released N-and O-linked glycans is the most robust glycomics strategy with respect to both sensitivity and quantitative reliability (5,6).…”
mentioning
confidence: 99%
“…Indeed, some organisms exploit this substrate promiscuity by diversifying the repertoire of available substrates (9). These "errors," which arise from the loose substrate specificity of the enzyme, can give rise to further diversification of an already heterogeneous population of glycoforms (10). Such variations may offer evolutionary advantages (11) or, alternatively, remain as an evolutionary relic (12).…”
mentioning
confidence: 99%
“…O-glycans cannot be removed from their sites enzymatically but have to be removed through alkaline b-elimination or hydrazinolysis, which in-turn denatures the peptide or proteins and thus does not allow any further site occupancy analyses to be undertaken. Technological advances in mass spectrometry are promising for improved N-and O-glycan analysis [26]. The ability of Quadrupole Time of Flight (QToF) instrumentation to facilitate MS experiments, especially on glycans which have been derivatised by permethylation, is allowing clear structural assignment of isomeric glycans [27].…”
Section: Glycomicsmentioning
confidence: 99%